Answer :

Let a be the first term and d be the common difference.


Given: a4 = 9


a6 + a13 = 40


We first find the common difference.


Now, Consider a4 = 9


a + (4 – 1)d = 9


a + 3d = 9 ……………………….(1)


Consider a6 + a13 = 40


a + (6 – 1)d + a + (13 – 1)d = 40


2a + 17d = 40 ………………..(2)


Subtracting twice of equation (1) from equation (2), we get,


11d = 22


d = 2


Common difference = d = 2


Put the value of d in equation (), we get


a = 9 – 3d


= 9 – 6


= 3


a = 3


The AP will be a, a + d, a + 2d, a + 3d,…


Thus the AP will be 3, 5, 7, 9,…


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Glimpses of IndiaGlimpses of IndiaGlimpses of India39 mins
Plane MirrorPlane MirrorPlane Mirror38 mins
Spherical MirrorSpherical MirrorSpherical Mirror35 mins
Concave MirrorConcave MirrorConcave Mirror33 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses